-6=-x+5-15-6x-8x+16

Simple and best practice solution for -6=-x+5-15-6x-8x+16 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -6=-x+5-15-6x-8x+16 equation:


Simplifying
-6 = -1x + 5 + -15 + -6x + -8x + 16

Reorder the terms:
-6 = 5 + -15 + 16 + -1x + -6x + -8x

Combine like terms: 5 + -15 = -10
-6 = -10 + 16 + -1x + -6x + -8x

Combine like terms: -10 + 16 = 6
-6 = 6 + -1x + -6x + -8x

Combine like terms: -1x + -6x = -7x
-6 = 6 + -7x + -8x

Combine like terms: -7x + -8x = -15x
-6 = 6 + -15x

Solving
-6 = 6 + -15x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '15x' to each side of the equation.
-6 + 15x = 6 + -15x + 15x

Combine like terms: -15x + 15x = 0
-6 + 15x = 6 + 0
-6 + 15x = 6

Add '6' to each side of the equation.
-6 + 6 + 15x = 6 + 6

Combine like terms: -6 + 6 = 0
0 + 15x = 6 + 6
15x = 6 + 6

Combine like terms: 6 + 6 = 12
15x = 12

Divide each side by '15'.
x = 0.8

Simplifying
x = 0.8

See similar equations:

| 3z-(-3)=-21 | | 2z-7=-7 | | 3x+5=4y+5 | | x+3x-6x=0 | | -4(x-1)-5x=41 | | 3a+5=25 | | 2b-1=-11 | | 14x^2+7x-70=0 | | .5X+y=5 | | 2(7n+8)=-96 | | 2x(x-33)+x=162 | | -4x-2(4x-14)=172 | | 72=2y+36 | | 5(x-2)+15+15+x=8 | | 82+(5x-40)=180 | | 4x+8-7x+5=0 | | 258=3x+8(4x+6) | | 13=5-m | | 0.24(24)+0.4x=0.12(18+x) | | 61+(4x-20)=180 | | 6x-5(-2x-5)=-167 | | 7x^2-35x-98=0 | | -x+-x+x+-x+-x+7= | | 2x(x-33)+x=33 | | -6+3(-x-6)=27 | | -6x+2(-5x-14)=148 | | 6x^2-60x-66=0 | | -4(3x-8)= | | 2x-2(-2x-18)=90 | | x+x+-x+5= | | 1/2x-y=2 | | s+2s= |

Equations solver categories